Cancer cell-secreted IGF2 instigates fibroblasts and bone marrow-derived vascular progenitor cells to promote cancer progression - Wen Wen Xu (Nature Portfolio, 2017)
Cancer cells can affect cancer progression by producing systemic effects. Here, the authors show that IGF2 produced by oesophageal cancer cells increases secretion of VEGF from cancer-associated fibroblasts resulting in systemic mobilization of bone marrow-derived cells and increased metastases.